Konsep etika pelajar menurut kh. m. hasyim asy’ari dalam kitab adab al `alim wa al-muta`allim - Usmaul Hasanah; Muhammad Mahfud (Jurnal Pendidikan Agama Islam Miazhar, 2021)
Student ethics according to KH. Hasyim Asy'ari in the book Adab al-Alim wa al Muta'allim presents a concept that in studying students are encouraged to be diligent and focused, giving serious attention to achieving the success of the learning process. Giving high respect to the teacher, because the teacher is someone who has been instrumental in directing and guiding students in studying, as well as being serious in seeking knowledge and as much as possible being able to practice their knowledge when they are finished seeking knowledge. The substance of the ethical concept of students offered and displayed by KH. Hasyim Asy'ari in the book Adāb al-'Ālim wa al-Muta'allim is divided into several parts that are fundamental to elementary matters relating to the ethics of students in the world of education. Such as the existence of students themselves and the ethics that should be attached to themselves which will later continue to how to be ethical towards teachers, proper learning ethics, and procedures for lessons (science) as well as books or textbooks. KH. Hasyim Asy'ari provides a concept or code of ethics as a good student. Looking at the ideas offered above, it is clear that Hasyim Asy'ari has the nuances of Sufism. According to him, the ideal goal of education is to form a high ethical society (akhlaqul karimah).